EVALUASI PROGRAM PENGEMBANGAN INDUSTRI PANGAN LOKAL DI SUMATERA BARAT - dian Hafizah; Rini Hakimi (Jurusan Agribisnis, Fakultas Pertanian, Perikanan dan Biologi Universitas Bangka Belitung, 2022)
This study aims to evaluate the implementation of the Local Food Industry Development program in West Sumatra. The data was collected through FGD with the stakeholders involved and then compared between the Technical Guidelines and Technical Guidelines for the West Sumatra Local Food Industry Development Program with the implementation in the field. The results obtained will be evaluated whether they are in accordance with the Technical Guidelines and Guidelines or not. Based on the results of the study, it was found that in general it had been implemented in accordance with the required technical guidelines and guidelines. Even so, there are several points that are not in accordance with the technical guidelines and technical guidelines due to several problems encountered in the field. However, this activity can continue to be carried out in order to further promote the use of local food in the community and further reduce the dominance of rice in people's food consumption